CMOS Current-Mode Circuits for Data Communications - Yuan, Fei (Analog Circuits and Signal Processing, 2007)
This book addresses the analysis and design principles of CMOS current mode circuits and their applications for data communications. The analytical methods and design principles are based on the characteristics of MOS devices applied to current CMOS technologies. Major topics include: design techniques for current mode circuits, electrical signaling for high speed data links, current-mode transmitters and receivers, switching noise and grounding of mixed mode circuits, a comparison of voltage-mode with current-mode circuits, ESD protection, and additional related topics. Examples are given of CMOS technologies from leading semiconductor companies and analyzed using the latest computer-aided design tools by leading design companies. CMOS Current-Mode Circuits for Data Communications is a valuable reference for circuit design engineers and hardware system engineers.